Circulating Ceramides- Are Origins Important for Sphingolipid Biomarkers and Treatments? - Mah, Michael; Febbraio, Mark; Turpin-Nolan, Sarah (Frontiers in Endocrinology, 2021)
Biomarkers are important tools for describing the adequacy or inadequacy of biological processes (to allow for the early and accurate diagnosis) and monitoring the biological effects of intervention strategies (to identify and develop optimal dose and treatment strategies). A number of lipid biomarkers are implicated in metabolic disease and the circulating levels of these biomarkers are used in clinical settings to predict and monitor disease severity. There is convincing evidence that specific circulating ceramide species can be used as biological predictors and markers of cardiovascular disease, atherosclerosis and type 2 diabetes mellitus. Here, we review the existing literature that investigated sphingolipids as biomarkers for metabolic disease prediction. What are the advantages and disadvantages? Are circulating ceramides predominantly produced in the liver? Will hepatic sphingolipid inhibitors be able to completely prevent and treat metabolic disease? As sphingolipids are being employed as biomarkers and potential metabolic disease treatments, we explore what is currently known and what still needs to be discovered.